MARRYING BECAUSE PREGNANCY ON THE PORCH OF MEDINA (GORONTALO) (A COMPARISON) - Slamet Bano, Irfan (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Lenggota Lo Pohutu (traditional wedding ceremony in Gorontalo) which is based on the philosophy of ‘adati hula-hula'a to sara’, sara' hula-hula'a to kitabullah, basically fulfils the validity of marriage without the need to consider the state of pregnancy as part of the prenuptial requirements. The only prenuptial requirement that is regulated is the Khatam Qur'an which aims to determine the bride's ability to read the Qur'an on the night of the engagement (Mopotilantahu). In the discussion of Islamic law, the coefficient of the cause of pregnancy should be more important than Khatam Qur'an, this is because the provision of provisions against deviant behaviour which is the urgency of the law in various propositions and sources of Islamic law, the limits of association, the prohibition of khalwat, and the punishment for the perpetrators of adultery are more widely discussed. For this reason, a causality approach that is historically normative is used. The results showed that the concept of Muayyidat Shar'iyyah is the main piece whose needs must be at an urgent stage on the issue of isbat nikah because of pregnancy. The local government acts as an executor (legality) as well as a facilitator, customary actors as mentors, and people who are required to obey, while the task of supervision is the responsibility of everyone. Religious leaders act as the first post to educate and the centre of study with customary actors. Based on its urgency, the legal theme applied is the optimisation of the role of supervision of deviant behaviours.